2013
DOI: 10.1155/2013/867537
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-124 Regulates the Proliferation of Colorectal Cancer Cells by TargetingiASPP

Abstract: MicroRNAs are a class of small, noncoding RNAs that function as critical regulators of gene expression by targeting mRNAs for translational repression or degradation. In this study, we demonstrate that expression of microRNA-124 (miR-124) is significantly downregulated in colorectal cancer tissues and cell lines, compared to the matched adjacent tissues. We identified and confirmed inhibitor of apoptosis-stimulating protein of p53 (iASPP) as a novel, direct target of miR-124 using target prediction algorithms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 31 publications
(30 reference statements)
1
41
0
Order By: Relevance
“…also reported that miR-124-3p is significantly down-regulated in colon cancer tissue as compared with that of adjacent non-tumor colorectal tissue [21]. miR-124-3p has also been shown to directly suppress iASPP (inhibitor of apoptosis stimulating protein of p53) protein expression and up-regulate NF-κB level, which suppresses cell proliferation of colon cancer cells [22]. Over-expression of miR-124-3p leads to increased apoptosis of colon cancer cells and reduces tumor growth in vitro and in vivo [21].…”
Section: Discussionmentioning
confidence: 99%
“…also reported that miR-124-3p is significantly down-regulated in colon cancer tissue as compared with that of adjacent non-tumor colorectal tissue [21]. miR-124-3p has also been shown to directly suppress iASPP (inhibitor of apoptosis stimulating protein of p53) protein expression and up-regulate NF-κB level, which suppresses cell proliferation of colon cancer cells [22]. Over-expression of miR-124-3p leads to increased apoptosis of colon cancer cells and reduces tumor growth in vitro and in vivo [21].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous reports. 27,28 We also performed knockdown of PRPS1 or RPIA in CRC cells; in both cases, this decreased the proliferation rate and attenuated the colony forming ability of showed that the miR-124-overexpressing xenograft tumors exhibited significantly lower levels of PRPS1 and RPIA protein ( Figure 6E). Intriguingly, negative correlations between PRPS1 mRNA as well as RPIA mRNA and miR-124 levels were observed ( Figure 6F).…”
Section: The Mir-124/prps1-rpia Axis Regulates Crc Cell Growth In Vitmentioning
confidence: 99%
“…As they are involved in regulation of wide array of biological processes including cell proliferation, differentiation, apoptosis, metastasis, angiogenesis, and immune response, miRNAs have been considered to be new approaches of tumor biomarkers for early cancer diagnosis and prognosis [9][10][11][12]. According to our literature retrieval, miR-124 has been demonstrated to play important roles in different types of cancer, such as hepatocellular carcinoma, breast cancer, colon cancer, lung cancer, and prostate cancer and plays an essential role in a couple of oncogenesis, including survival, growth, apoptosis, migration, and metastasis [13,14]. However, its roles in tumorigenesis of glioblastoma are still unknown.…”
Section: Introductionmentioning
confidence: 99%